Proteomic Analysis of Climatic Keratopathy Droplets - Menegay, Michelle (2008)
PURPOSE. To identify the proteins in the corneal droplets of climatic droplet keratopathy (CDK), a disease that results in the formation of droplets on the cornea. Progressive accumulation of droplets in CDK leads to visual loss. METHODS. Proteomic mass spectrometry of the CDK specimens was performed after fractionation of proteins in 4% to 20% SDS-polyacrylamide gels. Droplets were derived from two human donors. Immunohistochemistry with antibodies was performed to confirm the presence of identified proteins on donor tissues from patients with CDK and control subjects. RESULTS. Proteomic analyses revealed identification of 105 proteins in CDK specimens. Immunohistochemical analyses confirmed localization of annexin A2 and glyceraldehyde 3-dehydrogenase (GAPDH), proteins identified by proteomic analyses in CDK specimens. The proteins were subjected to analyses with the Kyoto Encyclopedia of Genes and Genomes (KEGG) Database which showed that a few biochemical pathways were more frequent for the identified proteins. CONCLUSIONS. Approximately 105 proteins were identified in CDK specimens, and a subset of them was confirmed by immunohistochemistry. Several of these may play a role in fibril or deposit formation.